1983
DOI: 10.1227/00006123-198310000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Renal Cell Carcinoma Mimicking a Meningioma

Abstract: We report a patient with renal cell carcinoma metastatic to the left trigone, which mimicked an intraventricular meningioma. The metastasis was recognized 1.3 years after removal of the primary tumor, a longer disease-free interval than any previously reported cases with brain metastases of renal cell carcinoma. The patient is now free of disease of years after resection and 17 years after the discovery of the primary tumor. Metastatic disease should be considered in all patients with prior resection of renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…According to some authors, the finding of an extensive perilesional edema is more characteristic of metastases than other intraventricular lesions 51–54. However, other authors have reported that intraventricular metastases can mimic meningiomas or colloid cysts 55,56…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, the finding of an extensive perilesional edema is more characteristic of metastases than other intraventricular lesions 51–54. However, other authors have reported that intraventricular metastases can mimic meningiomas or colloid cysts 55,56…”
Section: Discussionmentioning
confidence: 99%
“…A group of entities mimicking TM includes choroid plexus metastases of renal cell carcinoma with[16] or without[2445] intraventricular hemorrhage, glioblastoma multiforme,[49] and cavernous malformations. [1926]…”
Section: Discussionmentioning
confidence: 99%
“…Many cases of late brain metastases from RCC have been described in the literature;[ 1 , 2 , 6 , 9 , 11 , 12 , 14 , 15 , 16 , 20 , 21 , 25 , 27 ] however, few of them analyze the pathophysiology of the appearance of these metastases. The objective of this work is to discuss which biological pathways are responsible for the late appearance of these metastases analyzing eight cases.…”
Section: Introductionmentioning
confidence: 99%